Arylsulfonylmethyl isocyanides: a novel paradigm in organic synthesis. Issue 65 (16th July 2015) - Kaur, Tanpreet; Wadhwa, Preeti; Sharma, Anuj
<x xml:space="preserve">Abstract</x> p-Tosylmethyl isocyanide (TosMIC), an α-acidic isocyanide has emerged as a privileged reagent to access biologically relevant fused heterocycles and some natural products like (−)-ushikulide A, variolin B, porphobilinogen and mansouramycin B.